Comparative Effectiveness of mHealth-Supported Exercise Compared With Exercise Alone for People With Parkinson Disease: Randomized Controlled Pilot Study. Issue 2 (30th January 2019) - Ellis, Terry D; Cavanaugh, James T; DeAngelis, Tamara; Hendron, Kathryn; Thomas, Cathi A; Saint-Hilaire, Marie; Pencina, Karol; Latham, Nancy K
Abstract: Background: Declining physical activity commonly occurs in people with Parkinson disease (PD) and contributes to reduced functional capacity and quality of life. Objective: The purpose of this study was to explore the preliminary effectiveness, safety, and acceptability of a mobile health (mHealth)–mediated exercise program designed to promote sustained physical activity in people with PD. Design: This was a 12-month single-blind (assessor), pilot, comparative-effectiveness, randomized controlled study. Methods: An mHealth-mediated exercise program (walking with a pedometer plus engagement in planned exercise supported by a mobile health application) was compared over 1 year with an active control condition (walking with a pedometer and exercise only). There were 51 participants in a community setting with mild-to-moderately severe (Hoehn and Yahr stages 1–3) idiopathic PD. Daily steps and moderate-intensity minutes were measured using a step activity monitor for 1 week at baseline and again at 12 months. Secondary outcomes included the 6-Minute Walk Test, Parkinson Disease Questionnaire 39 mobility domain, safety, acceptability, and adherence. Results: Both groups increased daily steps, moderate-intensity minutes, and 6-Minute Walk Test, with no statistically significant between-group differences observed. In the less active subgroup, changes in daily steps and moderate-intensity minutes were clinically meaningful. An improvement in the Parkinson Disease Questionnaire 39 mobility score favored mHealth in the overall comparison and was statistically and clinically meaningful in the less active subgroup. Limitations: The limitation of the current study was the small sample size. Conclusions: Both groups improved physical activity compared with expected activity decline over 1 year. The addition of the mHealth app to the exercise intervention appeared to differentially benefit the more sedentary participants. Further study in a larger group of people with low activity at baseline is needed.